PUBLTC RELATTONS (PR) DI ERA SOCIAL MEDIA - Adhianty Nurjanah (IKOM UMY, 2015)
Public Relations (PR) is a mediator its public companies, both internal public and external public companies. A PR should be oble to heor, smell, feel and see the public opinion. The era of social media, which is characterized by the increasing use of online media such as Facebook, Twitter, You Tube, Plurk, etc, the duty of a PR company experienced major changes, because a PR not to mention hundreds of potential customers, but thousands and even millions more potential consumers in cyberspace, which can and are free to communicate, expressing their will without being dependent on the mainstream media, They can form their own online communities, whether based on occupation, hobby, or a brand. They can also share information through blogs, forums and mailing lisfs, as well as to network with Facebook and Friendster. The social medio have been able to revolutionize the way of communicating with bloggers, the Facebookers, the Friendsters, the owner of the account in Plukers and other Web 2.0 all of which are consumers, as well as publishers and influencers, Thus the company to still exist in the ero of social media, a PR company should be able to communicate actively and effectively with the public. Now PR does not use on troditional PR strategy, which is well informed, communication, marketing but olso with a PR strategy social media technology well.